National stereotypes: the construction of Argentine identity from immigrant life stories (Encuentros, 2025)
This work is part of an investigation titled “Construcciones de la identidad y la alteridad a partir del signo ‘inmigrante’ en el discurso político y legislativo argentino”. On this occasion, we work with a book published in 2011 by the National Directorate of Migration, that compiles thirty-seven stories about the lives of migrants from different parts of the world. We propose that the book, while composing representations of migrants, builds the identity of Argentines. Therefore, in this paper we investigate what representations -and stereotypes- about Argentines appear in the publication. We consider two strategies are used: 1) the paratexts of the book, where the Argentines themselves evaluate their specificities as a people, 2) the voice of foreigners, who evaluate Argentines in the context of their stories of lifetime. In this work, we analyze both strategies and the linguistic resources by which they are carried out. Our hypothesis is that the prologue and the closing of the book redirect the attention to the construction of an Argentine identity. Furthermore, both in the aforementioned paratexts and in the life stories themselves, a tension is generated between the purely receptive character that is postulated -not only for the government of Argentina, but for its citizens- and certain xenophobic attitudes. We frame our work in Critical Discourse Analysis and our methodology is qualitative.
Keywords: Migrants; National identity; Frames; Evaluation